Impact of Bacillus on Phthalides Accumulation in Angelica sinensis (Oliv.) by Stoichiometry and Microbial Diversity Analysis - Feng, Wei-Meng; Liu, Pei; Yan, Hui; Zhang, Sen; Shang, Er-Xin; Yu, Guang; Jiang, Shu; Qian, Da-Wei; Ma, Jun-Wei; Duan, Jin-Ao (Frontiers in Microbiology, 2021)
Plant-microorganism interaction in the rhizosphere is thought to play an important role in the formation of soil fertility, transformation and absorption of nutrients, growth and development of medicinal plants, and accumulation of medicinal ingredients. Yet, the role that they play in the phthalides accumulation of Angelica sinensis (Oliv.) Diels remains unclear. In the present study, we report a correlative analysis between rhizosphere microorganisms and phthalides accumulation in A. sinensis from Gansu, China where was the major production areas. Meanwhile, Bacillus was explored the potential functions in the plant growth and phthalide accumulation. Results revealed that the common bacterial species detected in six samples comprised 1150 OTUs which were involved in 368 genera, and predominant taxa include Actinobacteria, Acidobacteria, and Proteobacteria. The average contents of the six phthalides were 4.0329 mg/g. The correlation analysis indicated that 20 high abundance strains showed positive or negative correlations with phthalides accumulation. Flavobacterium, Nitrospira, Gaiella, Bradyrhizobium, Mycobacterium, Bacillus, RB41, Blastococcus, Nocardioides, and Solirubrobacter may be the key strains that affect phthalides accumulation on the genus level. By the plant-bacterial co-culture and fermentation, Bacillus which were isolated from rhizosphere soils can promote the plant growth, biomass accumulation and increased the contents of the butylidenephthalide (36%~415%) while the ligustilide (12~67%) was decreased. Altogether, there is an interaction between rhizosphere microorganisms and phthalides accumulation in A. sinensis, Bacillus could promote butylidenephthalide accumulation while inhibiting ligustilide accumulation.